RUANG INTERAKTIF-KREATIF DI KEMANG - Sudarmaya Fauzi; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2020)
Over time, the growth of the city increasingly triggers a diversity of activities that take place. One tendency of urban community activities is the need to exchange experiences and obtain a comfortable place to socialize and exchange experiences. These activities are no longer carried out at home or in the office, but in a place called Third place. Kemang is an area that was once a settlement now a commercial center called the